Determinasi nilai pH untuk memprediksi kualitas perairan pada kolong pascatambang timah di Pulau Bangka - Euis Asriani; Andri Kurniawan (Jurusan Akuakultur, Universitas Bangka Belitung, 2015)
The study in predicting quality of water in ex-tin mining lakes in Bangka Island aims to identify the condition of the waters through the measurement of various parameters of waters, formulating models of a possible relationship between various parameters of water at the pit measured and formulate the relationship parameters of pH with other water quality parameters. Sampling conducted research sites in each district / city in Bangka Island with cluster sampling. Measurement of water quality parameters include measurements of pH, dissolved oxygen (DO), temperature, turbidity, and the heavy metals polluted level. The relationship of all the results mathematically analyzed using multiple linear regression as a model of post-tin mining water quality. In the old lakes, obtained fairly linear relationship between temperature parameters pH, DO, and brightness with a correlation coefficient of R = 0.81 and coefficient of determination R2 = 65%. In both types of lakes, relationship model between pH with other parameters is not significant in linearity. Based on test results of heavy metals, some metals were detected in water samples was Pb, Cd and Fe.